The Bureaucratization of Collaborative Governance in Realizing Tourism Villages during the COVID-19 Pandemic in Winduaji Village, Paguyangan Brebes - ., Tobirin; Rokhman, Ali; Indiahono, Dwiyanto; Dadan, Sulyana (KnE Social Sciences, 2023)
The development of nature-based tourism that can be used as a way of empowering rural communities during the COVID-19 pandemic is expected to be a solution to improve the economic conditions of the community. The problem is that the village does not have the same perspective in developing nature-based tourism villages. As a result of this, various problems arise in the development of natural tourism. This study aims to analyze the collaborative governance process in building tourist villages, their problems, and solutions. The research method is descriptive qualitative, with the process of collecting data through in-depth interviews, observations, and FGDs. The results showed that collaboration between stakeholders often leads to horizontal conflicts, awareness of the COVID-19 process is difficult to build in tourism development, and collaborative governance is more bureaucratic. This research can conclude that the development of nature-based tourism is a solution during the COVID-19 pandemic, but building public awareness of the importance of COVID-19 health protocols in tourism services is an obstacle. In addition, the bureaucratization of the collaboration process of governance hinders the development of natural tourism. Keywords: tourism village, collaborative governance, COVID-19 pandemic